2016
DOI: 10.1186/s12913-016-1615-z
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of clinical networks in improving quality of care and patient outcomes: a systematic review of quantitative and qualitative studies

Abstract: BackgroundReorganisation of healthcare services into networks of clinical experts is increasing as a strategy to promote the uptake of evidence based practice and to improve patient care. This is reflected in significant financial investment in clinical networks. However, there is still some question as to whether clinical networks are effective vehicles for quality improvement. The aim of this systematic review was to ascertain the effectiveness of clinical networks and identify how successful networks improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
142
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(146 citation statements)
references
References 41 publications
(85 reference statements)
1
142
0
3
Order By: Relevance
“…23 A wide range of factors other than size alone influence performance, including the availability of resources, the quality of clinical leadership, and pre-existing relationships in the local health economy. [34][35][36][37][38][39][40] The time and resources involved in health service reorganisations such as scaling up organisations have often been underestimated, and anticipated benefits have not always been delivered. 20,[41][42][43] Although patients may value increased routes of access through scaling up, new access routes may not be well received by all patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…23 A wide range of factors other than size alone influence performance, including the availability of resources, the quality of clinical leadership, and pre-existing relationships in the local health economy. [34][35][36][37][38][39][40] The time and resources involved in health service reorganisations such as scaling up organisations have often been underestimated, and anticipated benefits have not always been delivered. 20,[41][42][43] Although patients may value increased routes of access through scaling up, new access routes may not be well received by all patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…To counter these challenges, previous studies have identified a number of factors that influence the effectiveness of collaborative work, including leadership, geographical proximity, stakeholders' knowledge and experience, resources, navigating between differing epistemological bases, managing relational complexity, opportunities for feedback, and the pay‐off for involvement (Baker & Irving, ; Brown et al, ; Currie, Enany, & Lockett, ; Fitzgerald & Harvey, ; Fung, ; Rycroft‐Malone et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular relevance to our work is the idea that coproduced research should be inclusive of relevant stakeholders. For example, Brown et al (, p. 9) highlight that a “culture of inclusivity” is crucial, whereas Rycroft‐Malone et al (, p. 24) argue that a lack of belonging has a “negative impact on engagement.” In this regard, the idea of inclusive coproduction has close similarities with research and theory on situated and social learning, especially the “communities of practice” concept, which describes how people engage in collective learning through shared domains of activity (Lave and Wenger, ). Significant here is the idea of active participation in shared practices, many of which can have a taken‐for‐granted quality as people build up shared repertoires and routines as they seek out and share information in the processes of problem‐solving.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these networks include collaborations between individuals and organisations across institutional and professional boundaries. These clinical networks thereby ensure quality of and access to care for patients, including those who require coordination of care across a range of settings 15. This is pursued through formation of networks of primary care professionals who jointly and locally provide care to a number of patients with dementia, desirably including at least one professional of the medical (eg, general practitioner), care (eg, community nurses or case managers) and welfare (eg, social workers) discipline.…”
Section: Methodsmentioning
confidence: 99%